How the value of information shapes the value of commitment or why the value of commitment does not vanish - Tanja Hörtnagl; Rudolf Kerschbamer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
This paper challenges recent results on the fragility of the value of commitment. It introduces a specific notion of the 'value of information' for a later-moving player about the action choice of a previously-moving player, gives conditions under which this value is positive and shows that a positive value of information for the latermoving player is sufficient for a positive value of commitment for the previouslymoving player. It then argues that the value of information for a later-moving player is unlikely to vanish in real-world applications, implying that the value of commitment for the previously-moving player does not vanish either.
Keywords: C72; D82; D83; L13; 330; Value of Information; Value of Commitment; Sequential Move Game; Imperfect Observability; Stackelberg Duopoly; First-Mover Advantage